EFEKTIVITAS ORGANISASI DALAM PENYELENGGARAAN PELAYANAN TANDA DAFTAR USAHA PARIWISATA (TDUP) DINAS KEBUDAYAAN DAN PARIWISATA KOTA SEMARANG - Dipta Kharisma; Tri Yuniningsih (Journal of Public Policy and Management Review, 2017)
Effectivity is essential as a form of accomplishment for what have been done by the stakeholders such as organization effectivity of Tourism Support Division in Tourism Business Registry services in Semarang. This study is conducted to describe and analyze whether the organization effectivity of Tourism Support Division in Tourism Business Registry service of Semarang has been effective, and to identify the hampering factors of Tourism Business Registry services in Semarang. The study is descriptive in which using qualitative approach. The data are collected by observation, interview, documentary studies, and library research. The result shows that the organization effectivity of Tourism Support Division in Tourism Business Registry services of Semarang has not been effective, as seen from the distant goal that is to provide a source of information about the regulation of Tourism Business for stakeholders. It is proved in amount of the number of stakeholders who do not own Tourism Business Registry. It is caused by several obstacles such as lack of human resources, inadequate facilities and infrastructure, minimum technology utilization, low awareness of entrepreneurs, and poor coordination in getting information. The suggestions given are holding regular and wide socialization to the businessmen about the importance of Tourism Business Registry, increasing the number of Human Resources (HR), and maximizing internet usage as an online based Tourism Business Registry.